DAMPAK PERUBAHAN SOSIAL BUDAYA TERHADAP PENDIDIKAN - Syamsidar Syamsidar (240-540X)
Social and cultural change is a symptom of the changing structure of the social and cultural patterns in a society. Socio-cultural changes are common symptoms that occur all time in every society. Changes that occur in accordance with the nature and human nature that always wants to make changes. While education is a form of manifestation of art and human culture that is constantly changing, evolving and as an alternative to the most rational and allows to make a change or development. The link between social change is education is the change in structure and function in the social system, which includes in it is education, because education in the society be it formal, informal and non-formal.